The Role of Toll-Like Receptor Pathways in the Mechanism of Type 1 Diabetes - Lien, Egil; Zipris, Danny (Current Molecular Medicine, 2009)
Toll-like receptors (TLRs) and the innate immune system play a key role in sensing and eliminating microbial infections. Interactions between TLRs and their ligands expressed by microbial pathogens induce a cascade of intracellular signaling events, culminating in the upregulation of proinflammatory pathways. Over the past two decades, numerous studies have established the role of the acquired immune system in the mechanism triggering type 1 diabetes (T1D). The recent discovery of TLRs has led to the recognition that the innate immune system may act, under some circumstances, as a double-edged sword. In addition to its beneficial role in host defense, it may lead to upregulation of proinflammatory autoimmune responses, islet destruction and diabetes. Indeed, recent observations are consistent with the hypothesis that altered innate functions exist in patients with T1D and could be part of the mechanism leading to disease onset, but the underlying mechanisms and the relevance of these alterations to early events triggering disease remain to be identified. Data obtained from mouse and rat models of T1D implicated TLR pathways in both disease induction and prevention. In both the NOD mouse and diabetes-prone BB (BBDP) rat, TLR upregulation can suppress disease. In the BioBreeding Diabetes Resistant (BBDR) rat, however, diabetes induced by virus infection involves the upregulation of TLR9 pathways, and generic TLR upregulation synergizes with virus infection on diabetes induction. Studies performed in mouse models of T1D with spontaneous or induced T1D implicate TLR1, TLR2, TLR3, and TLR7 in disease mechanisms. The finding that TLR pathways are involved in mediating islet inflammation holds great promise for identifying new molecules that could potentially be targeted to specifically suppress the autoimmune process in individuals at high risk for disease development. The potential link between TLR upregulation and autoimmunity emphasizes the need for caution in using new therapies involving TLR agonists as vaccine adjuvants.
Keywords: innate immunity